INNOVATIVE METHODS AND TECHNOLOGIES OF PHYSICAL EDUCATION OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Abdikamalov Xojabay Ismamutovich; Najimov Paraxat Ibraymovich (Proximus Journal Publishing, 2024)
The use of innovative technologies in the system of physical education at the university increases the efficiency and quality of physical education classes in modern conditions. Mastering the content of innovative technologies provides the specifics of a high degree of readiness for social and professional activities of the teacher and student. The introduction of the theoretical and methodological foundations of educational technologies in the pedagogical activity of the teacher, the change in the forms, methods and content of training forms the corresponding motivations and interests in physical culture and sports activity.
Keywords: Physical culture; students; methodological complex